Use of contingent valuation methods for eliciting the willingness to pay for sanitation in developing countries - Nguyen Hoang Thanh; Hoang Van Minh; Doan Thi Thu Huyen; Le Hong Chung; Hung Nguyen-Viet (2014)
Information about willingness to pay (WTP) of households for improved sanitation is essential for policy makers to expand the improved sanitation coverage in population. We conducted this systematic review on contingent valuation (CV) method to eliciting the WTP of people for improved sanitation, using various kind of CV methods, such as: Open-ended question, Payment card, Dichotomous choice and Bidding Game. The online search was performed in multiple electronic databases including MEDLINE, Pubmed, Web of Sciences and EMBASE. Some search engines namely Google or Google Scholar and expert consultations were also used. Twelve stated preference studies using contingent valuation methods for improved sanitation and related services were found, especially in Asia and Africa. Iterative bidding game and dichotomous choice questions were found both highly sensitive to tests of household consumption and income.